2022
DOI: 10.1177/17474930221093501
|View full text |Cite
|
Sign up to set email alerts
|

Fight INflammation to Improve outcome after aneurysmal Subarachnoid HEmorRhage (FINISHER) trial: Study protocol for a randomized controlled trial

Abstract: Rationale: Aneurysmal subarachnoid hemorrhage (SAH) has high morbidity and mortality. While the primary injury results from the initial bleeding and cannot currently be influenced, secondary injury through vasospasm and delayed cerebral ischemia worsens outcome and might be a target for interventions to improve outcome. To date, beside the aneurysm treatment to prevent re-bleeding and the administration of oral nimodipine, there is no therapy available, so novel treatment concepts are needed. Evidence suggests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…However, lower rate of pathologic ICP increase, more frequent utilization of intra-arterial spasmolysis for vasospasm treatment, and somewhat decreasing rate of systemic infections in the cohort during the study period might have contributed to better final outcome of our aSAH patients. As possible explanation for this lower burden of ICP and infection-related complications, changes in the conservative SAH management [ 3 ], and particularly the gradual reduction in the practice of using triple H therapy [ 14 ] should be mentioned. Fittingly, there was more frequent use of intra-arterial spasmolysis for vasospasm treatment in the investigated cohort during this time.…”
Section: Discussionmentioning
confidence: 99%
“…However, lower rate of pathologic ICP increase, more frequent utilization of intra-arterial spasmolysis for vasospasm treatment, and somewhat decreasing rate of systemic infections in the cohort during the study period might have contributed to better final outcome of our aSAH patients. As possible explanation for this lower burden of ICP and infection-related complications, changes in the conservative SAH management [ 3 ], and particularly the gradual reduction in the practice of using triple H therapy [ 14 ] should be mentioned. Fittingly, there was more frequent use of intra-arterial spasmolysis for vasospasm treatment in the investigated cohort during this time.…”
Section: Discussionmentioning
confidence: 99%
“…The first studies analyzing inflammation after SAH have attempted to identify a link between inflammation and the risk of cerebral vasospasm [ 26 , 27 ]. Recent studies also identified a higher risk of DCI with increasing inflammatory response after SAH [ 28 , 29 ]. However, this association is probably due to the involvement of inflammatory mediators in the coagulation cascades, resulting in microthrombosis and microcirculatory disturbances, and accordingly, a higher risk of DCI, rather being than related to the vasospasm of large intracranial vessels [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the increased downregulation of inflammatory cytokines by continuous dexamethasone administration can also contribute to the prevention of secondary SAH complications such as DCI. To assess the above-mentioned results and other potential mechanisms of the glucocorticoids effect, the organizers of a multi-center prospective trial analyzing the effect of treatment with dexamethasone on the SAH outcome are currently recruiting patients in Germany [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even a prophylactic DHC could potentially be beneficial 19 . Jabbarli The establishment of an EBI severity grading may also be helpful for a more reliable patient 14 selection as an inclusion criterion in studies evaluating therapies for EBI not only surgical but also medical treatments such as anti-inflammatory agents, which is the objective of the currently ongoing FINISHER trial 22 .…”
Section: Diagnostic and Therapeutic Implications Of Using An Ebi Grad...mentioning
confidence: 99%